Complications Associated with Erythropoietin Stimulating Agents (ESAs) in Patients with Metastatic Breast Cancer: A Surveillance, Epidemiology, and End Results (SEER)-Medicare Study - Chavez-MacGregor, Mariana (2011)
PURPOSE: To evaluate the patterns of use and the risk of thromboembolic events (TEE) associated with Erythropoietin Stimulating Agents (ESAs) in older patients with metastatic breast cancer receiving chemotherapy. METHODS: Retrospective study using the SEER-Medicare linked database. Stage IV breast cancer patients diagnosed from 1995–2005, treated with chemotherapy, ≥66 years old, with full coverage of Medicare A and B were included. ICD-9 and HCPCS codes were used to identify the use of ESAs, chemotherapy, and complications of therapy. Analyses included descriptive statistics and logistic regression. RESULTS: 2,266 women were included, 980 (43.3%) received ESAs and 1,286 (56.7%) did not. Patients diagnosed after 1999 or who received treatment with taxanes, anthracyclines or vinorelbine were more likely to receive ESAs. Patients receiving ESAs had higher rates of stroke (18.5% vs 15.1%, p=0.031); DVT (21.3% vs. 14.4%, p<0.001), other/unspecified TEE (19.8% vs 14.7%; p=0.001) and any clot (31.3% vs. 23.4%, p<0.0001). In multivariable analysis, patients receiving ESAs had increased risk for DVT (OR=1.36; 1.05–1.75), and any clot (OR=1.26; 1.02–1.57). A dose-dependent effect was evident for stroke, DVT, other TEE and any clot. CONCLUSION: In this cohort of patients, the use of ESAs increased the risk of TEEs, with a dose-dependent effect for stroke, DVT, other TEE and any clot. Our data shows that among patients treated with chemotherapy and ESAs for metastatic breast cancer, TEEs are a common event. Therefore caution is recommended when using these agents.